The role of the Ral/Exocyst pathway in structural plasticity at the Drosophila neuromuscular junction - Cristóvão, José Pedro Dias (2020)
ABSTRACT: Defects in synaptic morphology and activity-dependent plasticity are a hallmark of neurodevelopmental and neurodegenerative disorders. Neuronal structure is critical for determining the properties of neurons, yet very little is known about the membrane dynamics that controls synaptic morphology. It is therefore critical to know the basic mechanisms by which neurons acquire their shape and change it in response to activity. This capacity of response is called synaptic plasticity, and allows modifications to be made in both pre- and post- synaptic elements of the synaptic terminal and their synapses. Given that synaptic plasticity is key for neurons to adapt to stimuli, it is important to study and understand the mechanisms by which it occurs and how defects can affect function. In this study, using the Drosophila neuromuscular junction as model, we show that activity-dependent formation of new presynaptic boutons is compromised when Ral and exocyst function is impaired, suggesting that this pathway plays a central role in structural plasticity. Ral GTPase is a small GTPase from the Ras superfamily and the exocyst is a conserved protein complex that is an effector for several GTPases, which, collectively might serve to control where, when and how, are vesicles targeted to a specific exocytic place. Dissecting the signaling cascade triggered by the Ral/Exocyst pathway will be key to understand how intracellular trafficking participates in this form of plasticity.